Inhibitory activities of selected Sudanese medicinal plants on Porphyromonas gingivalis and matrix metalloproteinase-9 and isolation of bioactive compounds from Combretum hartmannianum (Schweinf) bark - Ebtihal Abdalla M. Mohieldin; Ali Mahmoud Muddathir; Tohru Mitsunaga (BMC, 2017)
Abstract Background Periodontal diseases are one of the major health problems and among the most important preventable global infectious diseases. Porphyromonas gingivalis is an anaerobic Gram-negative bacterium which has been strongly implicated in the etiology of periodontitis. Additionally, matrix metalloproteinases-9 (MMP-9) is an important factor contributing to periodontal tissue destruction by a variety of mechanisms. The purpose of this study was to evaluate the selected Sudanese medicinal plants against P. gingivalis bacteria and their inhibitory activities on MMP-9. Methods Sixty two methanolic and 50% ethanolic extracts from 24 plants species were tested for antibacterial activity against P. gingivalis using microplate dilution assay method to determine the minimum inhibitory concentration (MIC). The inhibitory activity of seven methanol extracts selected from the 62 extracts against MMP-9 was determined by Colorimetric Drug Discovery Kit. In search of bioactive lead compounds, Combretum hartmannianum bark which was found to be within the most active plant extracts was subjected to various chromatographic (medium pressure liquid chromatography, column chromatography on a Sephadex LH-20, preparative high performance liquid chromatography) and spectroscopic methods (liquid chromatography-mass spectrometry, Nuclear Magnetic Resonance (NMR)) to isolate and characterize flavogalonic acid dilactone and terchebulin as bioactive compounds. Results About 80% of the crude extracts provided a MIC value ≤4 mg/ml against bacteria. The extracts which revealed the highest potency were: methanolic extracts of Terminalia laxiflora (wood; MIC = 0.25 mg/ml) followed by Acacia totrtilis (bark), Ambrosia maritima (aerial part), Argemone mexicana (seed), C. hartmannianum (bark), Terminalia brownii (wood) and 50% ethanolic extract of T. brownii (bark) with MIC values of 0.5 mg/ml. T. laxiflora (wood) and C. hartmannianum (bark) which belong to combretaceae family showed an inhibitory activity over 50% at the concentration of 10 μg/ml against MMP-9. Additionally, MMP-9 was significantly inhibited by terchebulin with IC50 value of 6.7 μM. Conclusions To the best of our knowledge, flavogalonic acid dilactone and terchebulin were isolated from C. hartmannianium bark for the first time in this study. Because of terchebulin and some crude extracts acting on P. gingivalis bacteria and MMP-9 enzyme that would make them promising natural preference for preventing and treating periodontal diseases.